2007
DOI: 10.1002/ijc.22812
|View full text |Cite
|
Sign up to set email alerts
|

Variation in breast cancer hormone receptor and HER2 levels by etiologic factors: A population‐based analysis

Abstract: Evidence suggests that breast cancer hormone receptor status varies by etiologic factors, but studies have been inconsistent. In a population-based case-control study in Poland that included 2,386 cases and 2,502 controls, we assessed ER-a and PR status of tumors based on clinical records according to etiologic exposure data collected via interview. For 842 cancers, we evaluated ER-a, ER-b, PR and HER2 levels by semiquantitative microscopic scoring of immunostained tissue microarrays and a quantitative immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 29 publications
(34 reference statements)
5
43
1
2
Order By: Relevance
“…They hypothesized that low serum hormone levels in overweight or obese, premenopausal women cause up-regulation of ER and PR levels in normal breast epithelium, leading to an exaggerated hormone response after menopause. 47 In our study population, the median age at diagnosis of breast cancer was 11 years younger than that reported in US patients (50 years vs 61 years). 48 Our study supports the finding of Rodriguez-Cuevas et al, who reported that the average age at diagnosis of breast cancer was 51 years in Mexican patients.…”
Section: -39contrasting
confidence: 50%
See 1 more Smart Citation
“…They hypothesized that low serum hormone levels in overweight or obese, premenopausal women cause up-regulation of ER and PR levels in normal breast epithelium, leading to an exaggerated hormone response after menopause. 47 In our study population, the median age at diagnosis of breast cancer was 11 years younger than that reported in US patients (50 years vs 61 years). 48 Our study supports the finding of Rodriguez-Cuevas et al, who reported that the average age at diagnosis of breast cancer was 51 years in Mexican patients.…”
Section: -39contrasting
confidence: 50%
“…20 Another study demonstrated that the association between ER/ PR and HER2 expression and BMI varies according to menopause status. 47 In premenopausal women, BMI was associated inversely with hormone receptor expression; but, in postmenopausal women, BMI had a positive association with hormone receptor and HER2 levels. They hypothesized that low serum hormone levels in overweight or obese, premenopausal women cause up-regulation of ER and PR levels in normal breast epithelium, leading to an exaggerated hormone response after menopause.…”
Section: -39mentioning
confidence: 92%
“…Standard immunohistochemistry with antigen retrieval prior to antibody incubation was performed according to established protocols for estrogen receptor (ER, clone 6F11, dilution 1:200, Novocastra), progesterone receptor (PR, clone PgR636, dilution 1:1,000, Dako), human epidermal growth factor receptor-2 (HER2+, polyclonal, dilution 1:1,000, Dako), epidermal growth factor receptor (EGFR, clone 31G7, dilution 1:500, Zymed), and cytokeratin 5 (CK5, clone XM26, dilution 1:500, Novocastra) [3,4]. A single pathologist (MES) assessed the stains by examining microscopic TMA slides and scanned images of the TMA slides, using the Aperio TMA Lab system (http://www.aperio.com/), as previously described [4].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…A single pathologist (MES) assessed the stains by examining microscopic TMA slides and scanned images of the TMA slides, using the Aperio TMA Lab system (http://www.aperio.com/), as previously described [4]. Each TMA core was scored for adequacy (satisfactory, suboptimal or unsatisfactory), staining intensity (0 = negative, 1 = weak, 2 = intermediate, and 3 = strong), and percentage of cells stained (0-100%).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Breast cancer is a heterogeneous disease, and research suggests that subtypes may vary in their etiologies (1). Menopausal hormone therapy, particularly combined estrogen-progestagen therapy, has been shown to increase breast cancer risk and has been implicated in the increased incidence of breast cancer observed over the past three decades (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%